Kontroversi Revisi Undang-Undang Minerba Terhadap Hak Asasi Manusia Masyarakat Hukum Adat - Rusdiana, Shelvi; Fitri, Winda; Divia, Felysha Putri (Universitas Batanghari Jambi, 2023)
Law no. 3 of 2020 is predicted to be able to improve mineral and coal mining by integrating the concept of real participation in the community. In fact, the Minerba Law has sparked polemics on human rights issues. This research aims to find out what are the controversial regulations on the Human Rights of Indigenous Peoples contained in the Minerba Law and the community's efforts to fight for human rights contained in the Minerba Law. This research uses normative juridical methods, namely research starting from statutory regulations, books, scientific journals and websites. The results of the research are that there are several articles that have multiple interpretations regarding the rights of customary law communities which are detrimental to the community. This controversy has certainly drawn a response from the public whose efforts are to carry out a judicial review at the Constitutional Court. Constitutional Court Decision Number 37/PUU-XIX/2022 Revision of Law Number 4 of 2009 concerning Mineral and Coal Mining as partly amended by Law Number 11 of 2020 concerning Job Creation to the Constitution of the Republic of Indonesia seems to provide a wide path to oligarchic profit-seekers rather than paying attention to the welfare of the Indonesian people. Looking at the problems above, the role of regional government is a solution in making regional legal product policies that can provide solutions for empowering, fostering respect and protection of MHA as a subject of development.Â